Images of Cruelty, Schooling and Refuge Possibilities - Langer, Eduardo Daniel (2024)
This article describes the relationships between cruelty, schooling and the possibilitiesthat the school offers as a refuge in the face of the inexorable circumstances that sealthe fates of a large part of the population living in conditions marked by intensifyinginequalities. The work is based on a multiple design which included an audiovisualproduction workshop in 2022 and 2023 involving students and teachers from ahigh school in the Buenos Aires metropolitan region and the university. Throughthe biographical-narrative method, students have carried out in-depth interviews,collaborative work and activities shared in the same school with one of the teachersfor over three years. Research results express how, as perceived by high school studentsand teachers, the school serves as a space that saves others and themselves, a place ofsupport, as well as transmission and education, even amidst instances of cruelty intheir daily experiences.